Evaluation of right liver lobe size to serum albumin concentration ratio in predicting the presence of esophageal varices in cirrhotic patients taking endoscopy as gold standard (Journal of Fatima Jinnah Medical University, 2023)
Background: Cirrhosis with its complication is a major health concern in Pakistan. Endoscopy is an invasive and expensive modality for screening for esophageal varices which is one of the most common complication of liver cirrhosis. Research is being conducted to explore non-invasive markers that can replace this invasive technique. We aimed to evaluate the predictive value of the ratio of the size of the right lobe of liver to serum albumin concentration in prediction of the presence of esophageal varices.Methods: It was a cross-sectional study conducted at the Medicine Department, Ghurki Trust Teaching Hospital, Lahore from January 4 till July 31. The study included 297 patients of all the genders, aged 20-70 years, diagnosed cases of liver cirrhosis for at least 6 months and having suspected esophageal varices on right liver lobe size to serum albumin ratio >4.1. All the patients were subjected to upper GI endoscopy to confirm predicted varices. Data was analyzed using SPSS 23.0. PPV of the ratio was calculated. Post-stratification chi square was used to find association (p value
Keywords: Cirrhosis; Esophageal Varices; Right Liver Lobe Diameter to Serum Albumin Ratio